Impact of Vitamin D3 Supplementation on Neuropsychiatric Lupus: Mini-Mental State Examination and 99mTc ECD Brain SPECT Evaluation - Sultana, Nasreen; Ihsan, Md Amimul; Adnan, Sheikh Md; Eram, Abrar Faiaz; Nahar, Lutfun; Arefin, Md Saidul; Islam, Sheikh Nazrul (Bangladesh Journal of Medical Physics, 2025)
Neuropsychiatric lupus (NPSLE) is a severe manifestation of systemic lupus erythematosus (SLE) associated with cognitive impairment and brain perfusion abnormalities. Vitamin D deficiency, prevalent in SLE, has been implicated in worsening neuropsychiatric symptoms. This study evaluates the effects of Vitamin D3 supplementation on cognitive function and brain perfusion in patients with NPSLE. Thirty-four adults with NPSLE underwent Vitamin D3 supplementation. Baseline and post-supplementation assessments included serum Vitamin D levels, Mini-Mental State Examination (MMSE) scores for cognitive function, and 99m Tc ECD Brain SPECT imaging for brain perfusion. Pre- and post-supplementation parameters were compared using the Wilcoxon Signed Ranks test. Post-supplementation, the median Vitamin D level significantly increased from 18.5 ng/mL (IQR: 11.5–19.2) to 28.5 ng/mL (IQR: 24.2–31.5) (p < 0.001). Cognitive function improved markedly, with MMSE scores increasing from 24 (IQR: 23.7–26) to 26 (IQR: 26–28) (p < 0.001). Brain perfusion abnormalities, particularly in the frontal and precuneus regions, showed reductions, and Z-scores demonstrated a significant improvement (p = 0.032). Vitamin D3 supplementation significantly enhances serum Vitamin D levels, cognitive function, and brain perfusion in patients with NPSLE. These findings support the potential of Vitamin D3 as an adjunct therapy for mitigating neuropsychiatric symptoms in lupus, warranting further research to confirm long-term benefits. Ban. J. Med. Phys., Vol -16, Issue -1, 2025 : 11-19